Cardiovascular safety and effectiveness of vildagliptin in patients with type 2 diabetes mellitus: a 3-year, large-scale post-marketing surveillance in Japan. Issue 5 (3rd May 2020) - Ishida, Yosuke; Murayama, Hiroki; Shinfuku, Yohei; Taniguchi, Tomoko; Sasajima, Takayoshi; Oyama, Naotsugu
ABSTRACT: Objectives : The dipeptidyl peptidase-4 (DPP-4) inhibitor vildagliptin is indicated for type 2 diabetes mellitus (T2DM). However, the long-term safety, effectiveness, and clinical relationship with cardiovascular events of vildagliptin have not been evaluated in Japan. Methods : The authors conducted post-marketing surveillance (PMS) to evaluate the safety and effectiveness of vildagliptin in more than 3000 Japanese T2DM patients for up to 3 years. Main assessments included demographics, major adverse cardiovascular events (MACE), adverse events (AEs), adverse drug reactions (ADRs), and glycated hemoglobin (HbA1c). Results : In this PMS, 3831 patients (775 sites) were registered in April 2010 − April 2012. The safety analysis population comprised 3769 patients; 2085 patients were aged ≥65 years, and 240, 411, and 114 had renal impairment, hepatic impairment, and heart failure, respectively. The median treatment duration was 2.7 years. The incidence of MACE was 6.04 cases/1000 person-years, mostly attributable to cerebrovascular events (4.27 cases/1000 person-years). The AE and ADR incidences were 26.0% and 5.3%, respectively. The incidence of hypoglycemia was 0.6%. No significant changes in body weight occurred and mean change in HbA1c from baseline at final assessment was −0.74 ± 1.41% ( p < 0.0001). Conclusions : In real-world clinical settings, vildagliptin was well tolerated, with similar profiles as previously reported.